2018
DOI: 10.1007/s41050-018-0008-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Municipal Waste Disposal Methods on Community Health in Ibadan - Nigeria

Abstract: The generation of waste, and its disposal, collection, transport and processing are important for healthy ecosystems and the health of people. The negative health effects of waste management is the subject of a large literature. Two main health outcomes have been found to be statistically associated with waste exposure: cancer and congenital malformations. This research study was designed to examine the relationship of environmental characteristics with population health, and impacts of waste disposal methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 10 publications
1
22
1
Order By: Relevance
“…Parallel to water and sanitation facility access, domestic waste management is an equally important component of hygiene that impacts health. A study in Nigeria found adverse health effects stemming from improper domestic waste management [ 16 ]. The World Bank reported a large divide in domestic waste management in 2016, where the percentage of waste collection in low- to middle-income countries were less than the average global rates [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Parallel to water and sanitation facility access, domestic waste management is an equally important component of hygiene that impacts health. A study in Nigeria found adverse health effects stemming from improper domestic waste management [ 16 ]. The World Bank reported a large divide in domestic waste management in 2016, where the percentage of waste collection in low- to middle-income countries were less than the average global rates [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…14 In order to overcome these problems the best option would be to implement sustainable solid waste management programs based on socioeconomic, environmental, and technicalissues. 15,16 Factors that can influence the sustainability of sustainable waste are the behavior of sorting waste, the behavior of 3R and the difficulty of man-aging waste. 17 The driving factors that play a role in the sustainability of waste management include the role of community leaders, economic benefits, social benefits, environmental benefits, waste management networks, and stimulation and facilitation of local governments.…”
Section: Resultsmentioning
confidence: 99%
“…Refuse disposal method has also been found to significantly affect diarrhoea and other health conditions in developing regions. 35,36 Long duration of water storage increased the risk of diarrhoea as found in group A probably due to increased frequency of handling and proliferation of micro-organisms on storage.…”
Section: Discussionmentioning
confidence: 99%